NiMoO4 / Ni (OH) 2-coated NiPx layered structure catalyst and preparation method and application thereof
By forming a NiMoO4/Ni(OH)2@NiPx layered structure catalyst on a nickel substrate, the problems of insufficient exposure of active sites and poor conductivity of nickel phosphide catalysts are solved, and efficient and stable electrocatalytic hydrogen evolution reaction is achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411792844.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-08
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-08
AI Technical Summary
The existing nickel phosphide catalysts have insufficient exposure to active sites, poor hydrophilicity and gas evaporation in electrocatalytic reactions, and poor conductivity and stability due to the use of binders.
NiMoO4/Ni(OH)2@NiPx layered structure catalyst was used to prepare NiMoO4 and electrodeposit Ni(OH)2@NiPx composites through nickel substrate treatment and hydrothermal reaction to form a three-dimensional layered structure, avoiding the use of binder.
The hydrophilicity and gas evaporation of the catalyst are significantly improved, the exposure of active sites is optimized, the catalytic performance and stability of the hydrogen evolution reaction is improved, and the production cost is reduced.
Smart Images

Figure CN119753733A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrocatalysts, and specifically relates to a NiMoO4 / Ni(OH)2@NiP x Layered structure catalyst and preparation method and application thereof. Background Art
[0002] Water splitting electrocatalysis technology is considered to be a very promising method for clean hydrogen production. In this process, the hydrogen evolution reaction (HER) is a key step, which requires the catalyst to have high catalytic activity, good stability and low cost. Although precious metal catalysts (such as platinum) have shown excellent catalytic performance in the hydrogen evolution reaction, their high cost limits their large-scale application. In recent years, nickel phosphide (NiP x ) As a non-precious metal catalyst with great potential, it has attracted widespread attention due to its good electronic structure and corrosion resistance. Nickel phosphide has electronic properties similar to platinum and exhibits high catalytic activity in electrocatalytic reactions, so it is regarded as a powerful alternative to precious metal catalysts. Compared with precious metal catalysts, nickel phosphide not only has significant cost advantages, but also its good stability makes it not easy to degrade in long-term electrocatalytic reactions, showing good application prospects.
[0003] However, as an electrocatalyst, the activity of nickel phosphide is still insufficient compared to that of precious metal catalysts. The structural design of nickel phosphide catalysts still faces many challenges, which limit their widespread promotion in practical applications. First of all, the structure of the catalyst not only affects the effective exposure of the active sites, thereby limiting its catalytic efficiency, but also the unoptimized structure may lead to unsatisfactory wettability and gas repellency of the catalyst. Specifically, the contact between the catalyst and the electrolyte is insufficient, and hydrogen bubbles are easily accumulated on the surface of the catalyst, thereby hindering the reaction and affecting the smooth progress of the hydrogen evolution reaction. In addition, powdered nickel phosphide catalysts usually require the use of binders when combined with electrodes, which not only reduces the conductivity of the catalyst, but also may lead to a decrease in electrochemical performance. More seriously, the binder may degrade or fall off during long-term use, thereby reducing the effective active area of the catalyst and further reducing the catalytic efficiency. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a NiMoO4 / Ni(OH)2@NiP x The layered structure catalyst and its preparation method are intended to solve the problems of insufficient exposure of active sites, poor hydrophilicity and gas repellency, and poor conductivity and stability due to the use of binders in the prior art. The catalyst prepared by the present invention has a unique three-dimensional layered structure, exhibits excellent hydrophilicity and gas repellency, and exhibits excellent catalytic performance and long-lasting stability in the hydrogen evolution reaction.
[0005] To achieve the above object, the present invention provides a NiMoO4 / Ni(OH)2@NiP x The preparation method of the layered structure catalyst comprises the following steps: Step 1, nickel substrate treatment: ultrasonically clean the nickel substrate using dilute hydrochloric acid, deionized water and ethanol in sequence to remove the surface oxide layer and oil stains, and finally dry it naturally to obtain a clean nickel substrate.
[0006] Step 2, preparation of precursor NiMoO4: dissolve nickel salt and ammonium molybdate in deionized water and stir until the solution is uniform. Place the nickel substrate treated in step 1 in the solution and transfer it to a high-pressure reactor for hydrothermal reaction at a temperature of 100-160°C for 4-14 h. After the reaction is completed, cool to room temperature, take out the nickel substrate, wash it with deionized water and ethanol, and dry it in an oven at 60°C to obtain the precursor NiMoO4.
[0007] In this step, NiMoO4 with a rod-like array structure having a large specific surface area is formed on the nickel substrate through a hydrothermal reaction, which helps to increase the loading amount of subsequent active materials and serves as a fast channel for electron transfer in the hydrogen evolution reaction process.
[0008] Step 3: Electrodeposition of Ni(OH)2@NiP x Composite: Dissolve nickel nitrate, sodium hypophosphite (NaH2PO2) and ammonium fluoride in deionized water, stir until the solution is clear, and use the nickel substrate loaded with NiMoO4 prepared in step 2 as the cathode and the inert anode as the anode for electrodeposition at a current density of 10~500 mA / cm 2 , the temperature is 20~80 ℃, and the electrodeposition time is 1~120min. After the electrodeposition is completed, the nickel substrate is taken out, washed with deionized water and ethanol in turn, and dried in an oven at 60°C to obtain NiMoO4 / Ni(OH)2@NiP x catalyst.
[0009] Furthermore, the nickel salt in step 2 may be one or a mixture of nickel nitrate, nickel sulfate or nickel chloride.
[0010] Furthermore, in step 2, the concentration of nickel ions is 0.01-0.2 mol / L, and the molar ratio of nickel to molybdenum is 1:0.5-3.
[0011] Furthermore, in step 3, the concentration of nickel ions is 0.1-1.0 mol / L, and the molar ratio of nickel ions to ammonium fluoride is 1:1.0-3.0.
[0012] Furthermore, in step 3, the concentration of sodium hypophosphite is 0.1-1.0 mol / L.
[0013] Furthermore, the inert anode used in step 3 may be a titanium-plated precious metal coating electrode, a titanium-plated non-precious metal coating electrode or a graphite carbon rod.
[0014] On the other hand, the present invention also provides a NiMoO4 / Ni(OH)2@NiP prepared by the above method. x The catalyst has a three-dimensional layered structure, in which one-dimensional NiMoO4 micro / nanorods are used as a support, two-dimensional Ni(OH)2 nanosheets are grown on the NiMoO4 surface, and zero-dimensional nickel phosphide (NiP x ) nanoparticles are embedded in Ni(OH)2 nanosheets. This structure significantly improves the electrocatalytic hydrogen evolution performance of the catalyst through the synergistic effect of different dimensions.
[0015] In another aspect, the present invention provides NiMoO4 / Ni(OH)2@NiP x Application of hierarchical catalysts in hydrogen evolution reaction.
[0016] Beneficial effects of the present invention: The NiMoO4 / Ni(OH)2@NiPx catalyst provided by the present invention has excellent hydrophilicity (contact angle close to 0°) and good bubble repellency (bubble contact angle reaches 164°). The design of the three-dimensional layered structure effectively exposes more active sites and significantly improves the catalytic efficiency. 2 When the catalyst was subjected to the conditions of 24h, the prepared catalyst showed a low hydrogen evolution overpotential of only 77 mV and was able to operate stably for more than 100 hours at this current density, showing excellent stability. In addition, the catalyst was grown directly on the nickel substrate in a binder-free self-supporting manner. This design avoids the negative impact of the binder on conductivity and ensures excellent electrocatalytic performance. The use of low-cost non-precious metal raw materials further reduces the production cost of the catalyst, making the catalyst significantly economical and having the potential for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 NiMoO4 / Ni(OH)2@NiP prepared in Example 1 of the present invention x Scanning electron microscope image of Figure 2 NiMoO4 / Ni(OH)2@NiP prepared in Example 1 of the present invention x Transmission electron micrograph of Figure 3 NiMoO4 / Ni(OH)2@NiP prepared in Example 1 of the present invention x X-ray powder diffraction pattern of Figure 4 NiMoO4 / Ni(OH)2@NiP prepared in Example 1 of the present invention x Graphs of water drop contact angle and underwater bubble contact angle; Figure 5 The hydrogen evolution reaction performance diagram of NiMoO4 / Ni(OH)2@NiPx prepared in Example 1 of the present invention, Comparative Example 1, Comparative Example 2 and Comparative Example 3; Figure 6 NiMoO4 / Ni(OH)2@NiP prepared in Example 1 of the present invention x Hydrogen evolution reaction stability test diagram. DETAILED DESCRIPTION
[0019] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0020] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0021] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0022] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0023] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0024] Example 1 Step 1: Nickel substrate treatment: Take a nickel substrate with a size of 2 cm × 5 cm and place it in a 3 M dilute hydrochloric acid solution for ultrasonic cleaning for 5 minutes to remove the oxide layer and impurities on the surface. Then, wash it three times with deionized water and anhydrous ethanol in sequence and dry it at room temperature to obtain a clean nickel substrate.
[0025] Step 2: Preparation of NiMoO4 precursor: 2.4 mmol nickel nitrate (Ni(NO3)2·6H2O) and 0.6 mmol ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) was dissolved in 80 mL of deionized water and stirred until the solution was uniform. The above solution was transferred to a 100 mL high-pressure reactor, and the pretreated nickel substrate was vertically immersed in the solution. The concentration of nickel ions in the solution was 0.03 mol / L, and the molar ratio of nickel to molybdenum was 1:1.75. After the autoclave was sealed, a hydrothermal reaction was carried out at 150°C for 5 hours. After the reaction was completed, it was cooled to room temperature, the nickel substrate was taken out, cleaned with deionized water and ethanol, and dried in an oven at 60°C to obtain a nickel substrate loaded with NiMoO4.
[0026] Step 3: Electrodeposition of Ni(OH)2@NiP x Composite: Dissolve 20 mmol nickel nitrate, 20 mmol sodium hypophosphite and 25 mmol ammonium fluoride in 50 mL deionized water and stir until the solution is clear. The concentration of nickel ions in the solution is 0.4 mol / L, the concentration of sodium hypophosphite is 0.4 mol / L, and the concentration of ammonium fluoride is 0.5 mol / L. The nickel substrate loaded with NiMoO4 prepared in step 2 is used as the cathode and the inert graphite carbon rod is used as the anode. At a current density of 100 mA / cm 2 Under the condition of constant current electrodeposition, the deposition was carried out at 25 °C for 6 minutes. After the deposition was completed, the cathode was taken out, washed with deionized water and anhydrous ethanol in turn and dried, and finally NiMoO4 / Ni(OH)2@NiP was obtained. x Hierarchical catalysts.
[0027] Example 2 Step 1: Nickel substrate treatment: Take a nickel substrate with a size of 2 cm × 5 cm and place it in a 3 M dilute hydrochloric acid solution for ultrasonic cleaning for 5 minutes to remove the oxide layer and impurities on the surface. Then, wash it three times with deionized water and anhydrous ethanol in sequence and dry it at room temperature to obtain a clean nickel substrate.
[0028] Step 2: Preparation of NiMoO4 precursor: 3.2 mmol nickel nitrate (Ni(NO3)2·6H2O) and 0.8 mmol ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) was dissolved in 80 mL of deionized water and stirred until the solution was uniform. The above solution was transferred to a 100 mL high-pressure reactor, and the pretreated nickel substrate was vertically immersed in the solution. The concentration of nickel ions in the solution was 0.04 mol / L, and the molar ratio of nickel to molybdenum was 1:1.75. After the autoclave was sealed, a hydrothermal reaction was carried out at 120°C for 8 hours. After the reaction was completed, it was cooled to room temperature, the nickel substrate was taken out, cleaned with deionized water and ethanol, and dried in an oven at 60°C to obtain a nickel substrate loaded with NiMoO4.
[0029] Step 3: Electrodeposition of Ni(OH)2@NiP x Composite: Dissolve 10 mmol nickel nitrate, 10 mmol sodium hypophosphite and 25 mmol ammonium fluoride in 50 mL deionized water and stir until the solution is clear. The concentration of nickel ions in the solution is 0.2 mol / L, the concentration of sodium hypophosphite is 0.2 mol / L, and the concentration of ammonium fluoride is 0.5 mol / L. The nickel substrate loaded with NiMoO4 prepared in step 2 is used as the cathode and the inert graphite carbon rod is used as the anode. At a current density of 200 mA / cm 2 Under the condition of constant current electrodeposition, the deposition was carried out at 25 °C for 3 minutes. After the deposition was completed, the cathode was taken out, washed with deionized water and anhydrous ethanol in turn and dried, and finally NiMoO4 / Ni(OH)2@NiP was obtained. x Hierarchical catalysts.
[0030] Example 3 Step 1: Nickel substrate treatment: Take a nickel substrate with a size of 2 cm × 5 cm and place it in a 3 M dilute hydrochloric acid solution for ultrasonic cleaning for 5 minutes to remove the oxide layer and impurities on the surface. Then, wash it three times with deionized water and anhydrous ethanol in sequence and dry it at room temperature to obtain a clean nickel substrate.
[0031] Step 2: Preparation of NiMoO4 precursor: 1.6 mmol nickel nitrate (Ni(NO3)2·6H2O) and 0.4 mmol ammonium molybdate ((NH4)6Mo7O 24·4H2O) was dissolved in 80 mL of deionized water and stirred until the solution was uniform. The above solution was transferred to a 100 mL high-pressure reactor, and the pretreated nickel substrate was vertically immersed in the solution. The concentration of nickel ions in the solution was 0.02 mol / L, and the molar ratio of nickel to molybdenum was 1:1.75. After the autoclave was sealed, a hydrothermal reaction was carried out at 120°C for 12 hours. After the reaction was completed, it was cooled to room temperature, the nickel substrate was taken out, cleaned with deionized water and ethanol, and dried in an oven at 60°C to obtain a nickel substrate loaded with NiMoO4.
[0032] Step 3: Electrodeposition of Ni(OH)2@NiP x Composite: Dissolve 30 mmol nickel nitrate, 20 mmol sodium hypophosphite and 25 mmol ammonium fluoride in 50 mL deionized water and stir until the solution is clear. The concentration of nickel ions in the solution is 0.6 mol / L, the concentration of sodium hypophosphite is 0.4 mol / L, and the concentration of ammonium fluoride is 0.5 mol / L. The nickel substrate loaded with NiMoO4 prepared in step 2 is used as the cathode and the inert graphite carbon rod is used as the anode. At a current density of 50 mA / cm 2 Under the condition of constant current electrodeposition, the deposition was carried out at 25 °C for 12 minutes. After the deposition was completed, the cathode was taken out, washed with deionized water and anhydrous ethanol in turn and dried, and finally NiMoO4 / Ni(OH)2@NiP was obtained. x Hierarchical catalysts.
[0033] Example 4 Step 1: Nickel substrate treatment: Take a nickel substrate with a size of 2 cm × 5 cm and place it in a 3 M dilute hydrochloric acid solution for ultrasonic cleaning for 5 minutes to remove the oxide layer and impurities on the surface. Then, wash it three times with deionized water and anhydrous ethanol in sequence and dry it at room temperature to obtain a clean nickel substrate.
[0034] Step 2: Preparation of NiMoO4 precursor: 2.4 mmol nickel nitrate (Ni(NO3)2·6H2O) and 0.6 mmol ammonium molybdate ((NH4)6Mo7O 24 ·4H2O) was dissolved in 80 mL of deionized water and stirred until the solution was uniform. The above solution was transferred to a 100 mL high-pressure reactor, and the pretreated nickel substrate was vertically immersed in the solution. The concentration of nickel ions in the solution was 0.03 mol / L, and the molar ratio of nickel to molybdenum was 1:1.75. After the autoclave was sealed, a hydrothermal reaction was carried out at 120°C for 8 hours. After the reaction was completed, it was cooled to room temperature, the nickel substrate was taken out, cleaned with deionized water and ethanol, and dried in an oven at 60°C to obtain a nickel substrate loaded with NiMoO4.
[0035] Step 3: Electrodeposition of Ni(OH)2@NiPx Composite: Dissolve 10 mmol nickel nitrate, 10 mmol sodium hypophosphite and 15 mmol ammonium fluoride in 50 mL deionized water and stir until the solution is clear. The concentration of nickel ions in the solution is 0.2 mol / L, the concentration of sodium hypophosphite is 0.2 mol / L, and the concentration of ammonium fluoride is 0.3 mol / L. The nickel substrate loaded with NiMoO4 prepared in step 2 is used as the cathode and the titanium plated ruthenium electrode is used as the anode. At a current density of 10 mA / cm 2 Under the condition of constant current electrodeposition, the deposition was carried out at 50 °C for 60 minutes. After the deposition was completed, the cathode was taken out, washed with deionized water and anhydrous ethanol in turn and dried, and finally NiMoO4 / Ni(OH)2@NiP was obtained. x Hierarchical catalysts.
[0036] Physical characterization: NiMoO4 / Ni(OH)2@NiP obtained in Example 1 x The hierarchical catalyst was physically characterized and the results are as follows: NiMoO4 / Ni(OH)2@NiP x SEM images of Figure 1 ) shows a micro / nanorod array structure with a diameter of several micrometers. Its surface is rough and a large number of interwoven nanosheets are observed, with a size of about 30 to 50 nanometers. Transmission electron microscopy (TEM) image ( Figure 2 ) further revealed that a large number of nanosheet structures grew on the surface of the nanorods. In the enlarged areas 1 and 2, the lattice fringes corresponding to the Ni (111) crystal plane were clearly seen, with a spacing of 0.205 nm, indicating that the surface of the nanosheets was inlaid with NiP x Nanoparticles. X-ray diffraction pattern shows ( Figure 3 ), the sample diffraction peaks mainly correspond to the characteristic peaks of NiMoO4 (PDF#45-0142), as well as a weak Ni(OH)2 peak, indicating that Ni(OH)2 presents amorphous characteristics. In addition, the relative contents of NiMoO4 and Ni(OH)2 are high, while NiP x The presence of NiP is relatively limited, so it is not clearly shown in the XRD spectrum. x diffraction peaks.
[0037] Figure 4 (a) and (b) show the bare nickel substrate and NiMoO4 / Ni(OH)2@NiP, respectively. x The water contact angle test results of the catalyst. For the bare nickel substrate, the water contact angle is 136.8°, indicating that its surface is significantly hydrophobic. xThe water contact angle is close to 0°, indicating that it has excellent hydrophilicity and can fully contact with water, thereby improving the wetting degree of the electrolyte and helping to improve the activity of the catalyst. Figure 4 (c) and (d) are NiMoO4 / Ni(OH)2@NiP x The test results of underwater bubble contact angle of the catalyst. The bubble contact angle of the bare nickel substrate is 147.5°, indicating that it has a certain degree of gas repellency underwater; while NiMoO4 / Ni(OH)2@NiP x The bubble contact angle of NiMoO4 / Ni(OH)2@NiP is further increased to 164.6°, showing excellent gas repellency. This property can effectively prevent the accumulation of bubbles on the catalyst surface during hydrogen evolution, reduce the blockage of active sites, and thus improve the efficiency of hydrogen evolution reaction. x The catalyst exhibits excellent hydrophilicity and gas repellency due to its three-dimensional layered structure, which effectively optimizes the contact between the catalyst and the electrolyte and the release process of hydrogen bubbles, thus giving it excellent catalytic performance in the electrocatalytic hydrogen evolution reaction.
[0038] Application in hydrogen evolution reaction: NiMoO4 / Ni(OH)2@NiP prepared in Example 1 x The activity and stability of the catalyst in hydrogen evolution reaction were tested, and the results are as follows: (1) Activity test: NiMoO4 / Ni(OH)2@NiP was evaluated in 1 M KOH solution using a standard three-electrode system. x HER catalytic performance. According to the polarization curves obtained by linear sweep voltammetry (LSV) ( Figure 5 ) showed that the catalyst only needed an overpotential of 77 mV to drive 10 mA / cm in the hydrogen evolution reaction. 2 of current density.
[0039] (2) Stability test: at -10 mA / cm 2 At the current density of 1.5 mol / L, the catalyst can operate stably for 100 hours with almost no attenuation of its activity ( Figure 6 ).
[0040] Comparative Example 1 The difference from Example 1 is that sodium hypophosphite is not added to the electrolyte used in step 3, and a nickel molybdate / nickel hydroxide composite catalyst (NiMoO4 / Ni(OH)2) grown on a nickel substrate is obtained. The electrochemical activity test shows that at 10 mA / cm 2 At a current density of , the overpotential required for the hydrogen evolution reaction is 127 mV ( Figure 5 ), much higher than the NiMoO4 / Ni(OH)2@NiP prepared in Example 1 xCatalyst (77 mV).
[0041] Comparative Example 2 The difference from Example 1 is that the nickel substrate pretreated in step 1 is not subjected to step 2, but is directly used as the cathode in step 3 to obtain a nickel hydroxide@nickel phosphide composite catalyst (Ni(OH)2@NiP X ). The electrochemical activity test showed that at 10 mA / cm 2 At a current density of , the overpotential required for the hydrogen evolution reaction is 203 mV ( Figure 5 ), much higher than the NiMoO4 / Ni(OH)2@NiP prepared in Example 1 x Catalyst (77 mV).
[0042] Comparative Example 3 The difference from Example 1 is that the NiMoO4 prepared in step 2 is not subjected to subsequent electrodeposition of Ni(OH)2@NiP x The composite, that is, without step 3, and the rest remain the same. The nickel molybdate (NiMoO4) catalyst grown on the nickel substrate was obtained. The electrochemical activity test showed that at 10 mA / cm 2 At a current density of , the overpotential required for the hydrogen evolution reaction is 266 mV ( Figure 5 ), much higher than the NiMoO4 / Ni(OH)2@NiP prepared in Example 1 x Catalyst (77 mV).
[0043] In addition, if Figure 5 c, NiMoO4 / Ni(OH)2@NiP prepared in Example 1 x The catalyst has a lower Tafel slope (58.6 mV / dec) than the catalysts in Comparative Examples 1, 2 and 3, indicating that its hydrogen evolution reaction kinetics is faster. Figure 5 d shows that the catalyst also exhibits the largest electrochemical active area (70 mF / cm 2 ), indicating that the three-dimensional hierarchical structure is conducive to the exposure of active sites. These results show that NiMoO4 / Ni(OH)2@NiP x Hierarchical catalysts show excellent performance in hydrogen evolution reactions and have broad application prospects.
[0044] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A NiMoO4 / Ni(OH)2@NiP x A method for preparing a layered structure catalyst, characterized in that: The following steps are involved: Step 1, nickel substrate treatment: ultrasonically clean the nickel substrate with dilute hydrochloric acid, deionized water and ethanol in sequence to remove the surface oxide layer and oil stains and then dry naturally; Step 2, preparation of precursor NiMoO4: dissolve nickel salt and ammonium molybdate in deionized water, stir until the solution is uniform, place the nickel substrate treated in step 1 in the solution, and transfer it to a high-pressure reactor for hydrothermal reaction at a temperature of 100-160°C for 4-14 h. After the reaction is completed, cool to room temperature, take out the nickel substrate, wash it with deionized water and ethanol, and dry it in an oven at 60°C to obtain the precursor NiMoO4; Step 3: Electrodeposition of Ni(OH)2@NiP x Composite: Dissolve nickel nitrate, ammonium fluoride and sodium hypophosphite in deionized water, stir until the solution is clear, use the nickel substrate loaded with NiMoO4 prepared in step 2 as the working electrode and the inert anode as the anode for electrodeposition at a current density of 10-500 mA / cm 2 , the temperature is 20~80 ℃, the electrodeposition time is 1~120 min, after the electrodeposition is completed, the nickel substrate is taken out, washed with deionized water and ethanol in turn, and dried in an oven at 60°C to obtain NiMoO4 / Ni(OH)2@NiP x catalyst.
2. The preparation method according to claim 1, characterized in that: In step 2, the nickel salt is one or a mixture of nickel chloride, nickel sulfate or nickel nitrate, the concentration of nickel ions is 0.01-0.2 mol / L, and the molar ratio of nickel to molybdenum is 1:0.5-3.
3. The preparation method according to claim 1, characterized in that: In step 3, the concentration of nickel nitrate is 0.1-1.0 mol / L, and the molar ratio of nickel ion to ammonium fluoride is 1:1.0-3.
0.
4. The preparation method according to claim 1, characterized in that: The concentration of sodium hypophosphite in step 3 is 0.1~1.0 mol / L.
5. The preparation method according to claim 1, characterized in that: In step 3, the inert anode is a titanium-plated precious metal coating electrode, a titanium-plated non-precious metal coating electrode or a graphite carbon rod.
6. NiMoO4 / Ni(OH)2@NiP prepared by the preparation method of claims 1 to 5 x A layered structure catalyst, characterized in that The catalyst has a three-dimensional layered structure, in which the one-dimensional layered structure is NiMoO4 micro / nanorods as a support, the two-dimensional layered structure is Ni(OH)2 nanosheets grown on the NiMoO4 surface, and the zero-dimensional layered structure is NiP x The nanoparticles are embedded on the Ni(OH)2 nanosheets.
7. NiMoO4 / Ni(OH)2@NiP x Application of hierarchical catalysts in hydrogen evolution reaction.
Citation Information
Patent Citations
N-NiMoO4 / Ni3N electrode material and preparation method and application thereof
CN111215110A
Cited By
Pd / NiMoO4 / Ni foam composite electrode and preparation method and application thereof
CN121134921A